Symbolic Dynamics for Real Rational Maps - Cabral, João (2014)
This work is an attempt to study the dynamics of real rational maps f ab (x) = (x 2 - a) / (x 2 - b), using symbolic dynamics. It is given an example that illustrates how the topological entropy can be calculated using kneading theory and Markov partitions in this family of rational maps.